PROBLEMS OF USING CUSTOMER-ORIENTED MARKETING STRATEGY IN THE MANAGEMENT SYSTEM OF EDUCATIONAL INSTITUTIONS - Oleg Bogoyavlenskiy (ScienceRise, 2020)
The object of research: marketing activities in higher education to remain competitive.